Sharia Economic Law Analysis of Mud Bathing in Tiktok Live as Online Begging (Maqashid Syariah Approach) - Masyithoh, Luthfiyah Dewi; Amrah, Dwi Putra; Musthofa, Imron (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2024)
The phenomenon of live mud bathing content on TikTok has stirred controversy, being perceived as a manifestation of online begging. TikTok’s live streams attract significant viewership, allowing some participants to earn substantial sums in a single session. However, this practice raises ethical concerns and conflicts with the principles of Maqashid Sharia, particularly in upholding human dignity and avoiding harm. This study aims to systematically analyze the issue through the perspectives of Sharia Economic Law and Maqashid Sharia. The research synthesizes relevant references from scholarly books and journals using a literature review methodology. The analysis indicates that live mud bathing content on TikTok primarily results in financial losses rather than benefits for Indonesian viewers. Furthermore, the study proposes recommendations for the Minister of Religious Affairs to ensure that TikTok content in Indonesia adheres to educational standards and local regulations. The novelty of this research lies in its application of Sharia Economic Law and Maqashid Sharia principles to analyze a contemporary digital ethics issue. This study contributes to the discourse on Islamic jurisprudence and digital media ethics by critically evaluating the ethical dimensions of live mud bathing on TikTok. The findings underscore the need for regulatory measures and moral guidelines to mitigate the negative impact of such content, ensuring alignment with societal values and religious principles.